2016
DOI: 10.1371/journal.pone.0148288
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Density of Physicians and Suicide Rates in Japan: Nationwide Ecological Study Using a Spatial Bayesian Model

Abstract: BackgroundRegional disparity in suicide rates is a serious problem worldwide. One possible cause is unequal distribution of the health workforce, especially psychiatrists. Research about the association between regional physician numbers and suicide rates is therefore important but studies are rare. The objective of this study was to evaluate the association between physician numbers and suicide rates in Japan, by municipality.MethodsThe study included all the municipalities in Japan (n = 1,896). We estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 25 publications
3
40
0
Order By: Relevance
“…Spatial clustering of suicides might be influenced by amplified cultural acceptance 37 . Similar to a British study 38 our space–time model revealed changes in suicide risk patterns over time, a phenomenon that has thus far been disregarded 39 . The grand linear upward trend confirmed our hypothesis and is consistent with Hegerl et al .…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Spatial clustering of suicides might be influenced by amplified cultural acceptance 37 . Similar to a British study 38 our space–time model revealed changes in suicide risk patterns over time, a phenomenon that has thus far been disregarded 39 . The grand linear upward trend confirmed our hypothesis and is consistent with Hegerl et al .…”
Section: Discussionsupporting
confidence: 62%
“…In Finland and Australia, access to mental health services significantly diminishes risk 14 , 29 . The availability of at least one psychiatrist per 100,000 persons has protective effects against death by suicide in Japan 39 . However, in Germany 61% of depressed patients are treated by general practitioners 45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resource limitations in some low-to-middle income countries therefore limits access to these professionals. Negative associations have, for example, been found between per capita availability of mental health services and suicide rates in a number of countries [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, we found a positive relationship between primary care physician rate and suicide/homicide rate across all models. There is limited research on this topic; however, prior studies in countries outside the US have identified a positive relationship between physician density and suicide, for both psychiatrists and physicians in general [51,52]. These studies posited that areas with higher baseline suicide levels could attract more policy attention and subsequent allocation of physician resources; that primary care practice generally does not allow general practitioners to assess or address suicide; and that there is more accurate reporting of suicide from higher-income localities, which also have more physician resources and thus may confound the relationship.…”
Section: Discussionmentioning
confidence: 99%